Blood-Brain Barrier Overview: Structural and Functional Correlation - Abeer Alahmari (Neural Plasticity)
The blood-brain barrier (BBB) is a semipermeable and extremely selective system in the central nervous system of most vertebrates, that separates blood from the brain’s extracellular fluid. It plays a vital role in regulating the transport of necessary materials for brain function, furthermore, protecting it from foreign substances in the blood that could damage it. In this review, we searched in Google Scholar, Pubmed, Web of Science, and Saudi Digital Library for the various cells and components that support the development and function of this barrier, as well as the different pathways to transport the various molecules between blood and the brain. We also discussed the aspects that lead to BBB dysfunction and its neuropathological consequences, with the identification of some of the most important biomarkers that might be used as a biomarker to predict the BBB disturbances. This comprehensive overview of BBB will pave the way for future studies to focus on developing more specific targeting systems in material delivery as a future approach that assists in combinatorial therapy or nanotherapy to destroy or modify this barrier in pathological conditions such as brain tumors and brain stem cell carcinomas.